Optimalisasi Pelayanan Digital DPMPTSP Bukittinggi dalam Meningkatkan Literasi Digital Masyarakat - Suci Kurnia Ilahi (JURNAL ILMIAH NUSANTARA, 2026)
Digital transformation is a strategic step in realizing efficient and transparent public services. This study aims to analyze the optimization of digital services by DPMPTSP Bukittinggi in enhancing the community’s digital literacy. The research method used is descriptive qualitative with data collected through observation, interviews, and documentation of digital service activities. The findings indicate that the implementation of digital systems such as OSS and SIPATEN improves service efficiency and encourages citizens to actively engage with technology. In addition to accelerating licensing processes, digitalization contributes to a better understanding of online public services among the community. Therefore, optimizing digital services not only enhances the quality of public administration but also continuously strengthens society’s digital literacy.